WRITINGS AS A FORM OF OPPOSITION: MATHALIB LITERATURE IN THE FIRST THREE CENTURIES AH - TOPGÜL, MUHAMMED ENES (BURSA ILAHIYAT VAKFI, 2017)
The evolution of early Islamic literature cannot be explained merely by scientific reasons. Indeed, each work is a product of the social, political, scientific, and economic frame of its time. During the first century of the. 'Abbasid rule, Muslim society experienced various social movements, such as Shu'ubiyyah; meanwhile, Shi'i communities began to develop their identity. Both movements opted to write relevant works in a similar manner to take aim at their opponents; accordingly, they compiled the points that condemned their opponents or their assumptions in separate works. The general name for this literature is mathalib (defect, fault, slandering). It developed into two subgenres, namely, mathalib al-'Arab and mathalib al-sababah. The objective of this paper is to present the existence of this genre, which has yet to be subject to a self-contained study, to identify the authors of these works in the first three centuries AH, and to interpret the available data about this genre with regard to hadith history.
Keywords: Mathalib al-'Arab; mathalib al-sababah; defects of the Companions; Shu'ubiyyah